Endurance Training and Consumption of Hydroalcoholic Zingiber Officinale Extract Regulated PPARγ, PGC1-ɑ/TNF-ɑ Expression Level in Myocardial Infarction Rats - Monireh Omomi; Farzaneh Taghian; Gholamreza Sharifi (Jorjani Biomedicine Journal, 2022)
Background and objectives: Zingiber officinale extract can control cardiovascular risk factors. Moreover, endurance training may effectively rehabilitate myocardial infarction by strengthening the myocardial muscle tissue. In-silico analysis identified essential genes involved in the heart damage process based on data from the DisGeNET database. Hence, we estimated the affinity of chemical and bioactive molecules for PPARγ. Therefore, this study aimed to investigate the effect of endurance exercise alone or combined with Zingiber officinale extract on Myocardial infarction rats. Material and Methods: Twenty-five male rats were randomly divided into five groups, including (1) group of myocardial infarctions (MI) induced by subcutaneous injection of isoproterenol, (2) myocardial infarction+exercise (MI+EX), (3) myocardial infarction+Zingiber Officinale extraction administered orally (MI+GE), (4) myocardial infarction+exercise+Zingiber Officinale extract (MI+EX+GE), and (5) Control group. The qPCR-Real Time technique was used to measure the expression of PGC1-ɑ, PPARγ, and TNF-ɑ genes. We evaluated the concentration of Troponin-1 as a vital myocardial ischemia marker. Results: In bioinformatics analysis, we found that the PPARγ, PGC1-ɑ, and TNF-ɑ pathways were critical in heart injury. Also, the effects of Zingiber officinale on heart tissue were detected through PPARγ by drug design. Endurance training combined with Zingiber officinale consumption reduced the expression of TNF-ɑ, Troponin-1 and increased the PGC1-ɑ, PPARγ genes. Furthermore, consumption of Zingiber officinale extraction improved the levels of PGC1-ɑ, PPARγ, TNF-ɑ, and Troponin-1. Conclusion: Our data indicated that six weeks of endurance training and consumption of Zingiber officinale extract could reduce the relative expression of the TNF-ɑ and significantly increase the level of PGC1-ɑ, PPARγ.